Joint association of sedentary time and physical activity with abnormal heart rate recovery in young and middle-aged adults - Zhizhen Liu; Peiyun Zheng; Yong Fang; Jie Huang; Jia Huang; Liming Chen; Qiaoling Hu; Chunyan Zou; Jing Tao; Lidian Chen (BMC, 2024)
Abstract Background Abnormal heart rate recovery (HRR), representing cardiac autonomic dysfunction, is an important predictor of cardiovascular disease. Prolonged sedentary time (ST) is associated with a slower HRR. However, it is not clear how much moderate-to-vigorous physical activity (MVPA) is required to mitigate the adverse effects of sedentary behavior on HRR in young and middle-aged adults. This study aimed to examine the joint association of ST and MVPA with abnormal HRR in this population. Methods A cross-sectional analysis was conducted on 1253 participants (aged 20-50 years, 67.8% male) from an observational study assessing cardiopulmonary fitness in Fujian Province, China. HRR measured via cardiopulmonary exercise tests on a treadmill was calculated as the difference between heart rate at peak exercise and 2 min after exercise. When the HRR was ≤ 42 beats·minute−1 within this time, it was considered abnormal. ST and MVPA were assessed by the IPAQ-LF. Individuals were classified as having a low sedentary time (LST [< 6 h·day−1]) or high sedentary time (HST [≥ 6 h·day−1]) and according to their MVPA level (low MVPA [0-149 min·week−1], medium MVPA [150-299 min·week−1], high MVPA [≥ 300 min·week−1]). Finally, six ST-MVPA groups were derived. Associations between ST-MVPA groups with abnormal HRR incidence were examined using logistic regression models. Results 53.1% of the young and middle-aged adults had less than 300 min of MVPA per week. In model 2, adjusted for possible confounders (e.g. age, sex, current smoking status, current alcohol consumption, sleep status, body mass index), HST was associated with higher odds of an abnormal HRR compared to LST (odds ratio (OR) = 1.473, 95% confidence interval (CI) = 1.172-1.852). Compared with the reference group (HST and low MVPA), the HST and high MVPA groups have a lower chance of abnormal HRR (OR, 95% CI = 0.553, 0.385-0.795). Compared with individuals with HST and low MVPA, regardless of whether MVPA is low, medium, or high, the odds of abnormal HRR in individuals with LST is significantly reduced (OR, 95% CI = 0.515, 0.308-0.857 for LST and low MVPA; OR, 95% CI = 0.558, 0.345-0.902 for LST and medium MVPA; OR, 95% CI = 0.476, 0.326-0.668 for LST and high MVPA). Conclusion Higher amounts of MVPA appears to mitigate the increased odds of an abnormal HRR associated with HST for healthy young and middle-aged adults.